PENILAIAN TINGKAT KERENTANAN AIR TANAH TERHADAP PENCEMARAN BERDASARKAN METODE SIMPLE VERTICAL VULNERABILITY DI KECAMATAN DIWEK KABUPATEN JOMBANG - Nisa, Reyza Kusvahrun; Siswoyo, Hari; Hendrawan, Andre Primantyo (EnviroScienteae, 2024)
The water source that is widely used to meet the domestic needs of people in the Diwek District, Jombang Regency is ground water through the use of dug wells. The groundwater at this location has the potential to be polluted by industrial waste. To anticipate this, research is needed on assessing the level of intrinsic vulnerability of groundwater to pollution based on the physical properties of rocks. The aim of this research is to assess the level of intrinsic vulnerability of groundwater to pollution and map its distribution. This research was carried out on 24 samples of dug wells in the Diwek District area which were observed periodically for 5 months from July 2023 to November 2023. The assessment of the level of intrinsic vulnerability of groundwater to pollution was carried out using the Simple Vertical Vulnerability (SVV) method based on 3 parameters i.e. the type of water unsaturated zone material (La), recharge/percolation (Wu), and the thickness of the water unsaturated zone (Z). Based on the research results, it can be stated that the SVV index value during the research period ranged from 14.89 to 40.96 with 3 categories of groundwater vulnerability levels, namely medium, high and very high. The distribution of groundwater vulnerability levels in the research location is dominated by medium vulnerability with an area varying from 46% - 48% of the study area.